(untitled) (Mediscope, 2024)
Background: The outbreak of coronavirus disease 2019 (COVID-19) has become a large threat to global health due to its high contagious nature and varied mortality. Arterial hypertension represents one of the most common comorbidities in patients with COVID-19. Close connections between inflammation and blood pressure (BP) have been described, and inflammation plays a key role in the outcome for patients with COVID-19. Objective: This study aims to investigate the clinical characteristics of patients with hypertension admitted for COVID-19 treatment in Gazi Medical College Hospital (GMCH), Khulna, Bangladesh. Methods: This was a cross-sectional type of observational study on patients with hypertension who were diagnosed with COVID-19 based on laboratory and/or radiological findings and admitted to Gazi Medical College Hospital, Khulna, Bangladesh, from July 1 to July 31, 2021. In that timeframe, overall, 215 patients with COVID-19 were admitted. Among them, 37 patients having hypertension fulfilled the inclusion criteria for the study. Demographic, clinical, laboratory and radiological data of those 37 patients were recorded and analyzed. Results: Among 37 study subjects, 54.1% were female. The mean age of the patients was 59.6±13.9 years. Among the study subjects, diabetes (56.8%) was the most common comorbidity. Regarding laboratory parameters, the mean Hb of the patients was 11.4±1.9 g/dl. In addition, the mean random blood sugar (RBS) level was 11.6±2.9 mmol/l. Neutrophilia and lymphocytopenia were observed in 86.5% and 83.8% cases, respectively. The mean D-dimer (2.4 mg/l) and CRP (72.5 mg/l) levels were well above their normal limits. In high resolution CT scan of the chest (HRCT chest), bilateral lung involvement was present in 89.2% cases. Ground-glass appearance was the most frequent (91.9%) radiologic pattern. Among antihypertensive drugs, losartan potassium was the most frequently used category (29.7%). Total 7 (18.9%) patients were severely affected with COVID-19 and admitted to the ICU, requiring mechanical ventilation. During our study, 2 patients (5.4%) died either due to multiple organ dysfunction syndrome or cardio-respiratory failure. Conclusion: The study provides key information to better understand the clinical characteristics of patients with hypertension admitted for COVID-19 treatment, which may help physicians to identify the factors associated with adverse outcomes in this disease. Mediscope 2024;11(1): 34-40